Redescription and new records of Ontholestes brasilianus Bernhauer, 1906 (Coleoptera: Staphylinidae: Staphylininae) - Costa-Silva, Vinícius; Asenjo, Angélico; Newton, Alfred F.; Thyssen, Patricia J. (Zootaxa, 2018)
The genus Ontholestes Ganglbauer includes 35 species distributed mainly in Eurasia, with a few additional species in Africa and North and South America (Herman, 2001; Yang & Zhou, 2012; Smetana & Shavrin, 2013; Rougemont, 2016). According to Asenjo et al. (2013), the South American record of the Palearctic species Ontholestes murinus (Linnaeus, 1758) for Brazil made by J. Guérin (1953) seems doubtful. Ontholestes murinus was recorded for the first time outside the Palaearctic region by Smetana (1981), from Newfoundland, in Canada, as an adventive species (e.g., Downie and Arnett, 1996; Brunke et al., 2011), but its occurrence in Brazil remains to be confirmed; if the Guérin (1953) record was based on a mistaken identification or mislabeled specimen, this would reduce the number of species distributed in this region from two to one. With respect to O. brasilianus Bernhauer, although it has been confirmed for Peru, Brazil and Argentina (Herman, 2001; Asenjo et al., 2013; Newton, 2015; Newton & Caron, 2015), no specific localities of occurrence have been reported since its description in 1906. Thus, to solve problems of misidentification with Neotropical species of this genus, in this study we redescribe Ontholestes brasilianus and provide the first illustrations of the beetle including its aedeagus and a short key for South American species. Additionally, new records from South America are listed here.